2012
DOI: 10.2298/abs1201113g
|View full text |Cite
|
Sign up to set email alerts
|

Secondary metabolite production in Hypericum perforatum L. cell suspensions upon elicitation with fungal mycelia from Aspergillus flavus

Abstract: We investigated the production of phenylpropanoids (phenolic compounds, flavanols, flavonols and anthocyanins) and naphtodianthrones (hypericins) in elicited Hypericum perforatum L. cell suspensions. To determine whether secondary metabolite production could be enhanced, Hypericum cell suspensions were exposed to mycelia extract from the fungus Aspergillus flavus. Elicited Hypericum cell suspension cultures displayed reduced growth and viability and a modification of secondary metabolites production. Ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Present results showed that exogenously applied fungal mycelia extracts negatively affected cell viability and fresh biomass production of H. perforatum cell cultures. Such a result has already been reported when H. perforatum cell suspensions have been elicited with JA, SA and fungal mycelia from A. flavus (Gadzovska et al 2007(Gadzovska et al , 2013Gadzovska-Simic et al 2012). On the other side, JA significantly stimulated biomass production of H. perforatum cells (Walker et al 2002), while treatments with SA, P. cinnamoni and Agrobacterium failed to show any stimulatory effect on cell growth (Walker et al 2002;Tusevski et al 2014).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Present results showed that exogenously applied fungal mycelia extracts negatively affected cell viability and fresh biomass production of H. perforatum cell cultures. Such a result has already been reported when H. perforatum cell suspensions have been elicited with JA, SA and fungal mycelia from A. flavus (Gadzovska et al 2007(Gadzovska et al , 2013Gadzovska-Simic et al 2012). On the other side, JA significantly stimulated biomass production of H. perforatum cells (Walker et al 2002), while treatments with SA, P. cinnamoni and Agrobacterium failed to show any stimulatory effect on cell growth (Walker et al 2002;Tusevski et al 2014).…”
Section: Discussionsupporting
confidence: 76%
“…Fusarium was shown as superior elicitor in stimulation of TP and TF production, while all tested fungal elicitors gave a similar response with respect to TFL and TA accumulation. Phenylpropanoid production in H. perforatum cell suspensions has also been stimulated using JA, SA, A. flavus and Agrobacterium as elicitors (Gadzovska et al 2007(Gadzovska et al , 2013; Gadzovska-Simic et al 2012;Tusevski et al 2014). The b Fig.…”
Section: Phenylpropanoid and Naphtodianthrone Productions Of H Perfomentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have been carried out to investigate the effects of different elicitors on the accumulation of secondary metabolites in Hypericum in vitro cultures. We have previously studied the overproduction of phenylpropanoids and naphtodianthrones in H. perforatum in vitro cultures upon treatment with phytohormones (Gadzovska et al 2005) and various elicitors, such as jasmonic acid (Gadzovska et al 2007), Aspergillus flavus mycelia extract (Gadzovska-Simic et al 2012) and salicylic acid ). In addition, various in vitro cultures from H. perforatum have been tested for their ability to produce naphtodianthrones and acylphloroglucinols upon treatment with mannan, b-1,3-glucan, pectin, jasmonic acid, methyl jasmonate, salicylic acid, fungal elicitor Phytophthora cinnamoni and bacterial elicitor Agrobacterium tumefaciens (Kirakosyan et al 2000;Sirvent and Gibson 2002;Walker et al 2002;Pavlík et al 2007).…”
Section: Introductionmentioning
confidence: 99%